Good agricultural practices in an association of familiar coffee producers by means of clusters analysis - Rosa, Beatriz Terezinha; Borges, Luís Antônio Coimbra; Pereira, Sérgio Parreiras; Antonialli, Luíz Marcelo; Souza, Sára Maria Chalfoun; Baliza, Danielle Pereira (Coffee Science - ISSN 1984-3909, 2017)
Familiar farmers have attended to quality and differentiation requirements to achieve markets with higher values. The certification is a management tool that may be required in this context. The rules of certification are based on principles of Good Agricultural Practices. The aim in this study was characterize the good agricultural practices used in the coffee production by coffee producers of Association of Familiar Agriculturists of Santo Antonio do Amparo (AFASA), in Minas Gerais State, by means of Cluster analysis. The research was performed through a survey type structured questionnaire, which was answered by all Association members. The original questionnaire of the research was separated into two parts. However, in this study was used only the second part, which has 104 variables distributed in a rating scale: 1, “not applicable in the property”, 2, “not have or not carried out”, 3, “sometimes or partially”, 4, “always, or yes” in relation to practices done in the property. The data were tabulated and analyzed by SPSS software. It was calculated the cluster multivariate analysis, which has as objective to group the individuals (cases) with similar characteristics in function of a set of selected variables that separated, in this case, the producers in two different groups. In this study was discussed the variables that present significant differences higher than p< 0,05 by the test Qui-Square of Pearson between two groups of farmers. The farmers of group 2 exhibited characteristic of higher organization in relation to principles of Good Agricultural Practices.